METODE QUANTUM TEACHING BERBASIS QUIZIZZ DALAM MENINGKATKAN MOTIVASI SISWA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM KELAS X SMK DEWANTORO PURWOSARI PASURUAN - Khamilatus Sholikha M; Anang sholikhudin (STKIP Subang, 2026)
This research is motivated by the low learning motivation of students in Islamic Religious Education (PAI) subjects, which is frequently triggered by the use of monotonous learning methods that are less adaptive to technological advancements. To address this dynamic, the Quantum Teaching method—which focuses on creating a comfortable and enjoyable learning environment—was implemented and combined with the Quizizz application as an educational gamification medium. The purpose of this study is to determine how the Quizizz-assisted Quantum Teaching method is applied and its impact on increasing student learning motivation at SMK Dewantoro Purwosari. This study employs a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews with PAI teachers and students, and documentation studies. The data analysis process includes data reduction, data display, and drawing conclusions. The results of the study indicate that the implementation of the Quantum Teaching method through the TANDUR framework (Tumbuhkan/Enroll, Alami/Experience, Namai/Label, Demonstrasikan/Demonstrate, Ulangi/Review, and Rayakan/Celebrate), integrated with the interactive features of Quizizz, successfully transformed the classroom atmosphere into a more lively one. The use of interactive quizzes, leaderboards, and reflective memes on Quizizz effectively triggered healthy competition and student enthusiasm. The increase in learning motivation is evident from aspects such as students' active engagement in discussions, punctuality in submitting assignments, and positive responses during the learning process. It can be concluded that the combination of the Quantum Teaching method and the Quizizz application is effective in increasing students' learning motivation in PAI at SMK Dewantoro Purwosari.